Evaluation of Economic, Social and Environmental Effects of Low-Emission Energy Technologies Development in Poland: A Multi-Criteria Analysis with Application of a Fuzzy Analytic Hierarchy Process (FAHP) - Magdalena Ligus (Energies, 2017)
The European Commission as well as the Polish government are promoting sustainable use of energy sources as a part of the dominating sustainable development paradigm. The development of low-emission energy sources engages the challenges of gradual depletion of coal, oil and natural gas reserves, as well as the intensification of the greenhouse effect. The energy policy should take into account development of low-emission energy technologies that contribute mostly to meeting the goals of sustainable development in three dimensions: economic, social and environmental. This study aims to assess the extent to which five low-emission energy technologies contribute to social welfare in the scope of the concept of sustainable development. Heuristic methods, including fuzzy analytic hierarchy process (FAHP) are used to resolve the multi-goal problem in order to achieve the aim of this research. Research results show that economic goal is still the most important to the development of various low-emission energy technologies in Poland, followed by the social and environmental goals. Secondly, renewable energy technologies should be utilized instead of nuclear energy to meet sustainable development policy goals. Photovoltaics, followed by biomass and biogas are perceived as the most suitable renewable energy sources. Wind on-shore and wind of-shore are on third and fourth place, respectively.